Injury situations in Freestyle Ski Cross (SX): a video analysis of 33 cases - Randjelovic, S.; Heir, S.; Nordsletten, L.; Bere, T.; Bahr, R. (British Journal of Sports Medicine, 2014)
Background: Although injury risk in Freestyle Ski Cross (SX) is high, little is known about the situations leading up to time-loss injuries. Objective: To describe the situations leading up to time-loss injuries in elite Freestyle SX. Study design: Descriptive video analysis. Methods: Thirty-three video recordings of SX injuries reported through the International Ski Federation Injury Surveillance System for four World Cup seasons (2006/2007 through 2010) were obtained. Five experts in the fields of sport medicine and SX analysed each case to describe in detail the situation leading up to the injury (skiing situation and skier behaviour). Results: Injuries occurred in four different skiing situations: jumping (n=16), turning (n=8), jumping and turning (n=7) and rollers (n=2). All injured skiers lost control before time of injury (n=33), due to skier-opponent contact (n=13), technical errors (n=8) or inappropriate strategy (n=8), which led to a fall (n=29). Contact occurred in 21 of 33 cases, usually unintentional at landing or take-off, caused by the opponent (n=11) or injured skier (n=8). The technical error cases (n=8) were dominated by bad jumping technique (n=6) and too much inside lean in turning situations (n=2), while inappropriate course line and bad timing at take off (n=7) dominated the inappropriate strategy cases (n=8). Conclusions We identified four main injury situations in elite SX, dominated by jumping situations. The primary cause of injury was unintentional skier-opponent contact in jumping, bank turning and roller situations. Another common cause of injury was personal errors (inappropriate technique and strategy) at take-off and in turning situations.